Elementary school teachers' math anxiety and students' math learning: A large‐scale replication. Issue 4 (15th January 2021) - Schaeffer, Marjorie W.; Rozek, Christopher S.; Maloney, Erin A.; Berkowitz, Talia; Levine, Susan C.; Beilock, Sian L.
Abstract: A solid foundation in math is important for children's long‐term academic success. Many factors influence children's math learning—including the math content students are taught in school, the quality of their instruction, and the math attitudes of students' teachers. Using a large and diverse sample of first‐grade students ( n  = 551), we conducted a large‐scale replication of a previous study (Proceedings of the National Academy of Sciences of the USA, 2010, 1860; n  = 117), which found that girls in classes with highly math anxious teachers learned less math during the school year, as compared to girls whose math teachers were less anxious about math. With a larger sample, we found a negative relation between teachers' math anxiety and students' math achievement for both girls and boys, even after accounting for teachers' math ability and children's beginning of year math knowledge, replicating and extending those previous results. Our findings strengthen the support for the hypothesis that teachers' math anxiety is one factor that undermines children's math learning and could push students off‐track during their initial exposure to math in early elementary school. Abstract : Prior research showed that girls learned less math when their teachers were highly math anxious. In this large‐scale replication, we found that both boys and girls learn less math in classrooms with highly math anxious teachers, replicating and extending the previous study's findings.